2020
DOI: 10.3390/ijms21072368
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intracellular Magnesium and Mineral Depositions during Osteogenic Commitment of 3D Cultured Saos2 Cells

Abstract: In this study, we explore the behaviour of intracellular magnesium during bone phenotype modulation in a 3D cell model built to mimic osteogenesis. In addition, we measured the amount of magnesium in the mineral depositions generated during osteogenic induction. A two-fold increase of intracellular magnesium content was found, both at three and seven days from the induction of differentiation. By X-ray microscopy, we characterized the morphology and chemical composition of the mineral depositions secreted by 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Magnesium is an essential co-factor in the enzymatic pathways involved with energy, protein and lipid metabolism and the modulation of glucose transport through the cellular membrane [5][6][7][8]. Thus, magnesium serves as an important link between transport systems and metabolism, and its concentration in the cytoplasm is regulated in a highly precise manner [9][10][11]. Despite the importance of magnesium in the organism, there are various studies that indicate that a considerable percentage of the population may have magnesium intake lower than the optimum [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is an essential co-factor in the enzymatic pathways involved with energy, protein and lipid metabolism and the modulation of glucose transport through the cellular membrane [5][6][7][8]. Thus, magnesium serves as an important link between transport systems and metabolism, and its concentration in the cytoplasm is regulated in a highly precise manner [9][10][11]. Despite the importance of magnesium in the organism, there are various studies that indicate that a considerable percentage of the population may have magnesium intake lower than the optimum [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is also important for bone health. Interestingly, SaOS-2 cells display osteoblastic features similar to primary human osteoblastic cells and are often used as a model of osteogenic differentiation [ 20 , 46 ]. A recent review showed how optimal magnesium and vitamin D balance may improve bone metabolism and health outcomes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evident link between magnesium and cell proliferation, the role of magnesium in cancer cells is scarcely documented and often contradictory [ 13 , 14 , 15 ]; in particular, the role of magnesium in primary bone tumours has not yet been examined. It is worth noting that in physiological conditions, magnesium plays an important role in bone metabolism [ 16 , 17 , 18 ] and can influence osteoblast and osteoclast differentiation, affecting bone growth and remodelling [ 19 , 20 ]. This work aims to study the role of magnesium in the growth of cancer SaOS2 osteosarcoma cells, monitoring the cellular concentration and compartmentalization of the cation by means of an advanced cellular imaging technique, as well as the effect of magnesium on specific signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, metals are good subjects for x-ray fluorescence (XRF) microscopy, which exploits the excitation of the core electrons of atoms, thus generating the emission of x-rays characteristic of the elements in the sample. However, these techniques request x-ray sources, and even if laboratory sources are improving their performances in an impressive way [ 285 ], the difference in the results obtained by laboratory equipment and the synchrotron radiation sources are still noticeable [ 270 , 286 ].…”
Section: Methods To Evaluate Magnesium Statusmentioning
confidence: 99%
“…By this application on single cells analysis, for example, it was possible to highlight the different distribution of intracellular magnesium in cells sensitive and resistant to doxorubicin, in cells deprived of extracellular magnesium [ 265 , 289 ], or in cells in which different magnesium channels are modulated, as reported [ 265 , 282 ]. Finally, this powerful technique has recently allowed researchers to dissect the initial step of mineral deposition during osteogenic commitment, opening a window on magnesium involvement in these events [ 286 ].…”
Section: Methods To Evaluate Magnesium Statusmentioning
confidence: 99%